The prognostic value of serum amyloid A for long‐term mortality among patients with subclinical carotid atherosclerosis. (12th March 2019) - Mayer, Florian J.; Binder, Christoph J.; Krychtiuk, Konstantin A.; Schillinger, Martin; Minar, Erich; Hoke, Matthias
Abstract: Background and Purpose: Despite extensive research in the last decade, the role of serum amyloid A (SAA) in atherogenesis remains highly controversial. The aim of this study was therefore to assess whether SAA is associated with long‐term mortality in patients with subclinical carotid artery disease. Methods: One thousand sixty‐five patients with neurological asymptomatic carotid atherosclerosis as evaluated by duplex sonography were prospectively followed for cause‐specific mortality. Results: During a median of 11.8 years, a total of 549 deaths, including 362 cardiovascular deaths, were recorded. Patients who died within the follow‐up period had significantly higher baseline SAA serum levels compared to those who survived (12.9 vs 9.5 mg/dL; P < 0.001). In univariable Cox regression analysis, the risk of all‐cause and cardiovascular mortality significantly increased in patients with elevated serum levels of SAA (crude hazard ratio for cardiovascular mortality per increase of 1 SD of SAA levels was 1.14, 95% CI 1.08‐1.22], P < 0.0001). However, SAA lost its significance after adjusting for high‐sensitivity C‐reactive protein (hsCRP), suggesting that SAA might not be directly associated with atherogenesis, but rather be a mere reflection of the individual patient's inflammatory status. Conclusions: Serum amyloid A is not independently associated with (cardiovascular) mortality in patients with subclinical carotid atherosclerosis.